Sintagmas nominais superlativos encaixados em SNs definidos: ambiguidades de leitura - Valadas, Rita (Revista da Associação Portuguesa de Linguística, 2019)
This paper analyses the semantical ambiguity in sentences containing superlative structures of European Portuguese where the superlative nominal phrase is particularly embedded, viz. in a higher definite nominal phrase – e.g. “a montanhaN1 com o soloN2 mais rochoso”; “o caçadorN1 do javaliN2 mais pesado”. I show that, besides the typical interpretation, where the superlative NP does not require a comparison of the set of entities expressed by the higher noun (N1), another interpretation is available where two interdependent comparisons are at stake – one between the entities identified by the higher noun (N1) and another one between the entities identified by the lower noun (N2). In this second type of interpretation, the higher noun influences directly the semantics of the superlative NP, by acting as a linguistic restrictor of the superlative’s comparison set, and the embedded NP also directly influences the interpretation of the higher NP. Formally, this restriction must be encoded in the semantic representation of the superlative NP, since, as will be shown, the information of the higher noun must be included in the comparison set’s restrictions (C*). This phenomenon is conditioned by pragmatics, since the restrictive reading of the higher noun is only possible in a context where the comparison between the two types of entities makes sense. I will propose that the NP embedding context of the superlative NP should be regarded as a crucial element in the typology of linguistic restrictors of the comparison set.